PENGARUH PEMBERIAN HUKUMAN TERHADAP KEDISIPLINAN BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Ristiliana Hermanto (Universitas Batanghari Jambi, 2020)
Abstract This research aimed at knowing the influence of punishment toward student learning discipline on Economics subject at State Senior High School 5 Tapung. Quantitative approach was used in this research with Expost Facto. All students in the Academic Year of 2019/2020 learning on Economics subject were the population of this research. They were 335 students. The samples were 182 respondents. To analyze the research findings was using Simple linear regression analysis to test R Square. Based on the research findings, it was obtained that R Square was 0.2811 and the score of determination coefficient percentage was 28.11%. So, it could be concluded that the influence of punishment toward student learning discipline on Economics subject at State Senior High School 5 Tapung was 28.11%. Keywords: Punishment, Learning Disciplines